Environmental Regulations and Housing Costs - C. Nelson Arthur (C. Nelson and John Randolph, 2009)
Many communities across the nation still lack affordable housing. And many officials continue to claim that “affordable housing” is an oxymoron. Building inexpensively is impossible, they say, because there are too many regulations. Required environmental impact statements and habitat protection laws, they contend, drive up the costs of construction. But is this actually true? In a comprehensive study of the question, the authors of this eye-opening book separate fact from myth.